2019
DOI: 10.1002/jimd.12066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary treatment and amino acid supplementation in organic acidurias and urea‐cycle disorders: On the basis of information from a European multicenter registry

Abstract: Organic acidurias (OAD) and urea-cycle disorders (UCD) are rare inherited disorders affecting amino acid and protein metabolism. As dietary practice varies widely, we assessed their long-term prescribed dietary treatment against published guideline and studied plasma amino acids levels. We analyzed data from the first visit recorded in the European registry and network for intoxication type metabolic diseases (E-IMD, Chafea no. 2010 12 01). In total, 271 methylmalonic aciduria (MMA) and propionic aciduria (PA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…There are several possible reasons for this: 40% of mut patients have significant feeding difficulties leading to PEG or NG‐tube feeding contrasting to only 15% in the cblA group. A recent study by Molema et al 28 showed that in the E‐IMD MMA patient cohort, plasma l ‐valine and l ‐isoleucine levels were very low, mainly in patients receiving amino acid mix (AAM), despite median daily natural protein intake being at the recommended daily allowance. Patient subgroups were not further subdivided in that study.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible reasons for this: 40% of mut patients have significant feeding difficulties leading to PEG or NG‐tube feeding contrasting to only 15% in the cblA group. A recent study by Molema et al 28 showed that in the E‐IMD MMA patient cohort, plasma l ‐valine and l ‐isoleucine levels were very low, mainly in patients receiving amino acid mix (AAM), despite median daily natural protein intake being at the recommended daily allowance. Patient subgroups were not further subdivided in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Acute suppression of the megalin pathway can be achieved by inhibition with dibasic amino acids, as shown with cultured cells 16,52 and by bolus injection into human volunteers, 15 perfusion in patients with cancer to prevent nephrotoxicity of radiochemicals, 53 or oral gavage in rats. 16 Long-term supplementation with arginine in man is considered safe, 54 is part of the treatment of genetic diseases of the urea cycle, 55 and is commonly used by body builders. Long-term supplementation with lysine is used for prevention of gyrate atrophy in hereditary ornithinemia.…”
Section: Discussionmentioning
confidence: 99%
“…This study addresses dietary management with an AA mixture appropriate for PKU; however, the findings may be generalizable to other conditions that are managed with specific AA mixtures. These might include AA mixtures lacking methionine in homocystinuria [ 4 ], leucine, isoleucine and valine in maple syrup urine disease [ 5 ], phenylalanine and tyrosine in tyrosinemia [ 6 ], lysine and tryptophan in glutaric aciduria type 1 [ 7 ], and isoleucine and valine in some organic acidurias [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, phenylketonuria (PKU) represents the most common and significant disease entity, with an estimated global incidence of 7/100,000 [ 1 ], although birth incidence varies by ethnicity and consanguinity, and estimates are influenced by the level of ascertainment [ 2 ]. Many inherited disorders of AA metabolism require prompt initiation of treatment at birth and lifelong adherence to a protein-restricted diet supplemented with defined AA mixtures that lack specific AAs [ 3 , 4 , 5 , 6 , 7 , 8 ]. Important products downstream of a metabolic block may need to be supplemented, such as tyrosine in PKU, phenylalanine in tyrosinemia and cysteine in some forms of homocystinuria.…”
Section: Introductionmentioning
confidence: 99%